Seropositive Rheumatoid Arthritis Following Complete Remission of Antineutrophil Cytoplasmic Antibody–Associated Vasculitis With Renal Involvement: A Case Report - Aaron Shulkin; Naushad Abid; Mehmoodur Rasheed (ACR Open Rheumatology)
Seropositive rheumatoid arthritis (RA) and antineutrophil cytoplasmic antibody–associated vasculitis (AAV) are two autoimmune conditions with unique etiologies and clinical presentations. Although few reports have documented rare cases in which a single individual has both conditions at the same time, it is much rarer to see them in sequence of each other. Here, we report a 69‐year‐old man diagnosed with AAV before achieving remission following six years of treatment. Following two years of remission, he was subsequently diagnosed with seropositive RA. This case invites unique insights to further explore underlying etiologies of autoimmune diseases and the interrelationship between them.